Effectiveness of READY (Reading with Daddy) Training to Improve Fathers' Involvement in the Parenting and Language Skills of Preschool-Aged Children - Estrilla Widya Patrichia (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Parents who consist of father and mother should carry out co-parenting to provide an optimal parenting model to support child development. However, the role of fathers in parenting in most Indonesian families is still far from being balanced with the role of mothers, so that Indonesia is one of the countries that is called a ‘fatherless country’. An intervention program aimed at increasing paternal involvement is needed. The READY (Reading with Daddy) program is an intervention program based on the three-step approach model of Lewin's Field Theory, which not only aims to increase fathers' involvement in parenting but is also beneficial for improving the language skills of preschoolers. The program intervention carried out in one of the kindergartens in Bengkulu was proven to increase fathers' involvement in parenting and improve children's language skills. This program can be a reference for the development of father parenting programs in the future.Orang tua yang terdiri terdiri dari pasangan ayah dan ibu seyogyanya perlu melakukan pengasuhan bersama (co-parenting) untuk memberikan model pengasuhan yang optimal dalam mendukung perkembangan anak. Namun demikian, peran ayah dalam pengasuhan anak di sebagian besar keluarga Indonesia dirasakan masih jauh dari keseimbangan dengan peran ibu, sehingga Indonesia merupakan salah satu negara yang disebut sebagai fatherless country. Oleh karena itu, sebuah program intervensi yang bertujuan untuk meningkatkan keterlibatan ayah diperlukan. Program READY (Reading with Daddy) merupakan sebuah program intervensi yang berdasarkan pada pendekatan three-steps model dari Teori Medan Lewin (Lewin’s Field Theory), tidak hanya bertujuan untuk meningkatkan keterlibatan ayah dalam pengasuhan, namun juga bermanfaat untuk meningkatkan kemampuan bahasa anak usia prasekolah. Program intervensi yang dilakukan di salah satu sekolah PAUD di Bengkulu ini terbukti dapat meningkatkan keterlibatan ayah dalam pengasuhan dan juga meningkatkan kemampuan bahasa anak. Program ini dapat menjadi acuan untuk pengembangan program-program parenting bagi ayah selanjutnya.